How to choose the perfect gift for a client and attract his attention ("Journal "U". Economy. Management. Finance.", 2024)
In this article, we will look at how you can choose a gift for a client that will not only please him, but also help draw his attention to your company. We will offer some key tips and ideas so that you can make the most of gifts as a marketing tool.
Keywords: gifts for customers; attracting attention; marketing tool; effective way